User Acceptance Test dan Penerapan Model ADDIE pada Media Pembelajaran Interaktif Pengenalan Profesi - Ari Nurul Alfian; Yoga Rifai; Rita Wahyuni Arifin; Rika Apriani; Indri Ayu Lestari; Dwi Ismiyana Putri (Prosiding SISFOTEK, 2024)
Digital technologies such as computers and handheld devices enhance student engagement and motivation and accelerate learning. Vocational introduction subjects are taught using a package book, a minimal tool for explaining the material becomes a reason for introducing interactive learning media for the introduction of various professions in students at Islamic High School Al-Hilal. The learning media development model used is the ADDIE model which includes Analysis, Design, Development, Implementation and Evaluation. The media testing was conducted using Blackbox Testing and User Acceptance Test (UAT). The results of the Blackbox testing were 100% valid and the UAT results were 92% of the applications were highly qualified from the total of 20 respondents. Learning media can help the process of effective learning activities and make it easier for students to understand the introductory material of a variety of professions.